2006
DOI: 10.1007/s11150-005-6698-y
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of the Gap Between Desired and Actual Fertility: The Case of Spain

Abstract: Fertility, Desired number of children, Unemployment, Short-term contracts, Religion, J13, J2, J6, Z13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 38 publications
0
38
0
5
Order By: Relevance
“…Several factors contribute to this mismatch between preferences and outcomes. They include competing career and leisure preferences, inability to find the right partner, marriage and partnership disruption, disagreement between partners, and the fact that many women and men face unstable employment conditions, economic difficulties, problems with combining work and childrearing, health problems, or infertility (Bongaarts 2002;Adsera 2006a;Morgan and Rackin 2010;Iacovou and Tavares 2011;Testa, Cavalli, and Rosina 2011). 13 Considering that couples in most European countries use reliable contraception and women often have access to abortion or emergency contraception, one might find it surprising that the observed differences in Europe are not even larger.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors contribute to this mismatch between preferences and outcomes. They include competing career and leisure preferences, inability to find the right partner, marriage and partnership disruption, disagreement between partners, and the fact that many women and men face unstable employment conditions, economic difficulties, problems with combining work and childrearing, health problems, or infertility (Bongaarts 2002;Adsera 2006a;Morgan and Rackin 2010;Iacovou and Tavares 2011;Testa, Cavalli, and Rosina 2011). 13 Considering that couples in most European countries use reliable contraception and women often have access to abortion or emergency contraception, one might find it surprising that the observed differences in Europe are not even larger.…”
Section: Discussion Main Findingsmentioning
confidence: 99%
“…Neither long-term experience of below-replacement fertility nor major social and economic upheavals or cultural and technological changes seem to have altered the widespread perception that having two children is ideal, both personally and for society. The factors identified in earlier studies as influencing fertility ideals and preferences, such as religiosity (Adsera 2006a), unemployment and labor market position (Adsera 2006b), experience of single living (Waite, Goldscheider, and Witsberger 1986), number of siblings and siblings' fertility (Axinn, Clarkberg, and Thornton 1994), as well as rising family instability, might be expected to erode the two-child family ideal as societies progressively become more secular, actual family size shrinks, more women enter the labor market, employment becomes more precarious, and more children grow up in unstable family environments. It can be argued that these forces have contributed to the observed gradual increase in the prevalence of the one-child ideal, but so far have not made any significant dent in the widespread adherence to a two-child family norm.…”
Section: Why An Ideal Of Two?mentioning
confidence: 99%
“…The empirical literature investigating the fall in fertility focuses almost only on women's economic conditions and on actual fertility rates, somewhat neglecting the fact that: 1) in EU countries, the desired fertility rate is significantly higher than the actual rate (Eurostat 2001;Adsera 2006). 2)…”
Section: Introductionmentioning
confidence: 99%
“…Hope and trust in God's grace, hope to solve the economic problems due to increased salary are among the interesting findings of this study. Studies have shown that fertility rate is changed in many communities according to the intensity of religious beliefs [46]. Couples with similar educational backgrounds or similar cultural or religious beliefs tend to take similar decisions related to reproduction [47].…”
Section: Discussionmentioning
confidence: 99%